2020
DOI: 10.1093/brain/awaa277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, cellular, and connectomic characterization of the brain regions commonly plagued by glioma

Abstract: For decades, it has been known that gliomas follow a non-random spatial distribution, appearing more often in some brain regions (e.g. the insula) compared to others (e.g. the occipital lobe). A better understanding of the localization patterns of gliomas could provide clues to the origins of these types of tumours, and consequently inform treatment targets. Following hypotheses derived from prior research into neuropsychiatric disease and cancer, gliomas may be expected to localize to brain regions characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 64 publications
5
66
0
Order By: Relevance
“…Our findings contribute to this literature by illustrating, in human patients, that glioma localization follows intrinsic functional and structural connectivity networks. This result is consistent with prior work from our group demonstrating that gliomas localize to functional brain hubs (Mandal et al, 2020).…”
Section: Network Spread Of Glioma Tumorssupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings contribute to this literature by illustrating, in human patients, that glioma localization follows intrinsic functional and structural connectivity networks. This result is consistent with prior work from our group demonstrating that gliomas localize to functional brain hubs (Mandal et al, 2020).…”
Section: Network Spread Of Glioma Tumorssupporting
confidence: 93%
“…In contrast to early ideas that gliomas originate from mature glial cells in the same locations where they are observed, current theories imply that tumors originate from neurogenic niches in the subventricular zone (SVZ), from which they then migrate to populate distributed brain areas (Jiang and Uhrbom, 2012;Lee et al, 2018;Sanai et al, 2005). This idea is supported by genomic evidence from patients (Lee et al, 2018) as well as the observation of significantly elevated glioma frequency surrounding neurogenic niches (Mandal et al, 2020). In parallel, other research has indicated that glioma stem cells travel along previously healthy brain structures, including blood vessels and white matter tracts, suggesting that large-scale connectivity networks may help describe glioma migration (Cuddapah et al, 2014;Gillespie and Monje, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Although the origin of glioma is still a matter of debate, it has been hypothesised that oligodendrocyte precursor cells (OPCs) are the cellular source of this type of tumour [ 52 ], which is supported by the fact that gliomas can be transformed into cancer cells through experimental manipulation [ 53 ]. We have recently shown that glioma incidence is higher in regions populated by OPCs, such as the temporal and frontal cortices [ 29 ]. On the contrary, excitatory and inhibitory neurons, which are directly associated with the GS [ 11 ], show a different distribution pattern, with decreased populations in medial temporal and frontal cortices [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the negative correlation between tumour incidence and regional coupling with the GS may reflect the differential cell organisation of the underlying tissue. Alternatively, but not mutually exclusively, we have also shown that glioma incidence is higher in regions with high functional connectedness regardless of tumour grade [ 29 ]. This preferential tumour localisation follows intrinsic functional connectivity networks, possibly reflecting tumour cell migration along neuronal networks that support glioma cell proliferation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation